(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The research examines the specifics of cognitive linguistics regarding developing communicative competence and forming students’ linguistic personalities. Attention is paid to the essence of cognitive linguistics, the history of the emergence of this direction, and the current state of research. The article analyzes the ways, methods, and forms of cognitive linguistics application in the educational process to form the student’s linguistic personality and develop communicative competence. The structure of the concept is presented for the simplified perception of a specific phenomenon by a student of a philological specialty. The study aims to reveal the role of cognitive linguistics in developing communicative competence and forming a student’s linguistic personality. The object of research is cognitive linguistics as a linguistic direction. Research methods. Such research methods as description, analysis and synthesis, generalization, and linguistic analysis were used in the work. The work examines the issue of cognitive linguistics in terms of the development of communicative competence and the formation of students’ linguistic personalities. The essence of the concept of "cognitive linguistics," its direction, principles, and principles are revealed. The history of the emergence of cognitive linguistics as a linguistic direction and the current state of research are described. Cognitive linguistics’ impact on forming a student’s communicative competence is described. The student’s types of thinking are analyzed, in particular, abstract, professional, critical, fast, and systematic. The case method is a key cognitive linguistics method used during educational activities. The proof of the values of the method is implemented, and the stages of the case method are demonstrated with the help of a graphic image. The article provides ways of forming the student’s communicative competence through cognitive linguistics. The advantages and disadvantages of each method are described. The construction of the concept is carried out, which contributes to the student’s faster perception of the topic and the types of concepts given.